Transmission Channel of Agriculture Food Import Tariff to Stunting Prevalence - Maya Hendrietta Montolalu; Jean F.J. Timban; Ellen G. Tangkere (Jurnal Penelitian Pendidikan IPA, 2024)
Increases in food prices affect poverty in a way that poor consumer is harmed due to the high proportion of their budget they spent on food. Stunting prevalence might be instigated by several factors such as access to food and nutrition intake, genetic and environment. This research aims to analyse the effect of food import tariffs towards the stunting prevalence of children aged under 5 (five) across districts in Indonesia, and we explore the indirect relationship between stunting prevalence and trade policy. This research uses quantitative descriptive research methods, utilizing both primary and secondary data. Primary data were obtained through the distribution of questionnaires, followed by Focus Group. Secondary data were obtained from relevant institutions such as the Central Statistics Agency, research journals, and related books. The method of data analysis in the study uses quantitative analysis with a mathematical model. The results showed that tariffs can reduce the consumption of foods that serve in the intake of dietary nutrients such as calories, protein and fat. As a result, food intake affects the prevalence of stunting. Trade liberalisation can have a beneficial impact on child health. The effects of trade liberalisation on stunting through the food channel include: a) trade has a significant effect on calorie, protein, and fat intake, b) intake of these nutrients has a significant effect on child stunting.